Ab initio study of F-centers in alkali halides - Hoya, Joaquín (2017)
The structural and electronic properties of an electron trapped at vacant anion site in alkali halides are investigated using first principles electronic structure calculations with the supercell method. In order to determine the spatial electronic charge density and band structure of the studied systems we used the Augmented Plane Waves plus local orbital (APW + lo) method in the framework of the Density Functional Theory (DFT), considering the Wu and Cohen parametrization of the generalized gradient approximation (WCGGA) for the exchange and correlation energy, and the modification of Tran and Blaha to the Becke and Johnson exchange potential (mBJ method). We discuss the improvements in the description of the defect levels induced by the vacancies using mBJ compared to WCGGA. Additionally, we revisit the experiment to perform a new determination of the UV/Vis absorption energies in F-centers. In the theoretical framework used, we demonstrate that the bound electron at the F-center is localized within a sphere with diameter twice the lattice parameter. From the comparison of our theoretical predictions with the Mollwo-Ivey relation that comes from this new experiment, we show that the mBJ method predicts accurately the energy band gaps and gives better energy values for the s-p transitions that give rise to the optical absorption energies.